Age‐specific outcomes from the first round of HPV screening in unvaccinated women: Observational study from the English cervical screening pilot. (18th January 2022) - Rebolj, Matejka; Mathews, Christopher S.; Pesola, Francesca; Cuschieri, Kate; Denton, Karin; Kitchener, Henry; ,
Abstract: Objective: To report detailed age‐specific outcomes from the first round of an English pilot studying the implementation of high‐risk human papillomavirus (HR‐HPV) testing in primary cervical screening. Design: Observational study with screening in 2013–2016, followed by two early recalls and/or colposcopy until the end of 2019. Setting: Six NHS laboratory sites. Population: A total of 1 341 584 women undergoing screening with HR‐HPV testing or liquid‐based cytology (LBC). Methods: Early recall tests and colposcopies were recommended, depending on the nature of the screening‐detected abnormality. Main outcome measures: We reported standard screening process indicators, e.g. proportions with an abnormality, including high‐grade cervical intraepithelial neoplasia (CIN2+) or cancer, and the positive predictive value (PPV) of colposcopy for CIN2+, by screening test and age group. Results: Among unvaccinated women screened with HR‐HPV testing at age 24–29 years, 26.9% had a positive test and 10.4% were directly referred to colposcopy following cytology triage, with a PPV for CIN2+ of 47%. At 50–64 years of age, these proportions were much lower: 5.3%, 1.2% and 27%, respectively. The proportions of women testing positive for HR‐HPV without cytological abnormalities, whose early recall HR‐HPV tests returned negative results, were similar across the age spans: 54% at 24–29 years and 55% at 50–64 years. Two‐thirds of infections at any age were linked to non‐16/18 genotypes. Among women with CIN2, CIN3 or cervical cancer, however, the proportion of non‐16/18 infections increased with age. As expected, the detection of abnormalities was lower following screening with LBC. Conclusions: These data provide a reliable reference for future epidemiological studies, including those concerning the effectiveness of HPV vaccination. Tweetable abstract: Data from the English pilot study provide a comprehensive overview of abnormalities detected through HPV screening. Tweetable abstract: Data from the English pilot study provide a comprehensive overview of abnormalities detected through HPV screening.